COLLABORATIVE LEARNING: BOOSTING QAWAID MASTERY WITH STAD MODEL - Muhammad Jundi; Laily Fitriani; Anhar Aquil (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
This research aims to investigate the use of the Student Teams Achievement Divisions (STAD) Cooperative Learning Model in enhancing collaboration among students in the Arabic qawaid material. The study examines the technical implementation steps of STAD and evaluates its impact on students' awareness of collaboration. A qualitative research approach with a case study design was employed. The participants consisted of students engaged in the implementation of STAD. Data were collected through classroom observations, interviews, and document analysis. The findings revealed that the technical implementation steps of STAD significantly contribute to improving collaboration among students. The students exhibited increased awareness of the importance of collaboration in achieving common academic goals. However, it was also found that enhancing collaboration requires consistent time and effort. This research holds important implications for the development of cooperative learning in the educational environment and provides recommendations for teachers and educational practitioners to effectively implement STAD and enhance collaboration among students.